Autoavaliação institucional: os desafios para o aperfeiçoamento de ações educativas - Carelle, Ana Claudia (2020)
This study results from the search for the improvement of the management action for the Technical Course in Nutrition and Dietetics at Etec de Guaianazes, where the author performs activities as a teacher and as coordinator. Therefore, the general objective was to explore and analyze information made available by the Institutional Evaluation System (IES), generated through the WebSAI platform seeking to identify the existence of interdependence between the Technical Schools belonging to the Paula Souza State Center of Technological Education (CEETEPS). For this, convergent and divergent aspects between teachers and students were investigated, related to 06 six management factors: 1) Teaching conditions; 2) School performance; 3) School management; 4) Pedagogical management; 5) Educational environment, and 6) Satisfaction. In the end, the work presents an intervention model for the school. The presentation of the results is made in the Multi paper format that is an innovative proposal, for the area of Education, exhibition, and dissemination of the results of the research that guides the investigative action for the treatment of the data that is now understood from the perspective of the collection - cumulative form - that is, to each set of data investigated, analyses and synthesis are performed that sensitize and guide the mapping of the work, offering to mean to subsequent actions. The methodology was organized considering 3 distinct but interconnected phases for the development of work/research was divided. They are: phase 1: to compare institutional data(macro universe: 150,004 students) with the data available from the Technical Course in Nutrition of Guaianazes (micro-universe: 174), both collected in 2018, aiming to identify, or not, the interdependence between the technical schools of CEETEPS; phase 2: explore information for the year 2017, justified by the application, identical, of questions for 15,037 teachers and 156,869 students, linked to the 151 courses offered in 223 CEETEPS units. In phase 3, the answers of 208 students of the Technical Course in Nutrition and Dietetics of Etec de Guaianazes were collected in 2017. The research was driven by two important aspects arising from the exploration of these data: the first discusses the difficulties that students encounter when studying the proposed contents; and the second, taking into account the "findings" of this study/research, presents the bases and a self-assessment model for the Technical Course in Nutrition and Dietetics (MODAV-TecNutri). This model is inspired by principles and assumptions that guide the National System of Higher Education (2014) and the Quality Indicators of High School (2018). Thus, MODAV-TecNutri was organized in 4 phases, 5 axes, and 7 dimensions. The methodology integrated techniques for collecting and analyzing quantitative and qualitative data. For the advancement of the work, it was necessary to formulate different phases of action. The present work will be presented only in phases 1 (ex-ante), 2 (process), and 3 (product). The final results of this proposal for intervention, presented in the Multi paper model, suggest that the proposed indicators — 1) coherence between the aspects defined in the official documents and the institutional reality; 2) functionality for achieving the proposed goals; and 3) property of viability based on ethical precepts regarding the diversity of those involved - are effective for the development of a proposal for self-assessment of the Technical Course in Nutrition and Dietetics (MODAV-TecNut), since they can guide the management action proposing the use of evaluative results.